Overview of the PMBOK® guide short cuts for PMP® certification - Ó Conchúir, Deasún; SpringerLink (Berlin, Heidelberg Springer Berlin Heidelberg XVI, 2011)
This book is for everyone who wants a readable introduction to best practice Project Management, as described by the "PMBOK[registered] Guide, 4th Edition" of the Project Management Institute (PMI), 'the world's leading association for the project management profession'. It is particularly useful for applicants for the PMI's PMP[registered] (Project Management Professional) and CAPM[registered] (Certified Associate of Project Management) examinations, which are based mostly on the "PMBOK[registered] Guide". This book can also be studied alone by anyone as a general introduction.
Chapter 1 Introducing Project Management. - Chapter 2 Understanding the PMBOK(R) Guide. - Chapter 3: Process Groups & Knowledge Areas. - Chapter 4 Integration Management Processes. - Chapter 5 Scope Management Processes. - Chapter 6 Time Management Processes. - Chapter 7 Cost Management Processes. - Chapter 8 Quality Management Processes. - Chapter 9 Human Resource Management Processes. - Chapter 10 Communications Management Processes. - Chapter 11 Risk Management Processes. - Chapter 12 Procurement Management Processes. - Chapter 13 Preparing for the PMP(R) Examination.
Keywords: Project management -- Handbooks, manuals, etc; Electronic books